Relación de la edad cronológica con la maduración ósea cervical mediante el método de Baccetti - Julca Lévano, Juan Carlos (2019)
Introduction: It is important to assess the ideal moment in which both biological and structural changes occur in the growth and development of the jaws, to identify at what moment pubertal growth begins in young patients and to correct both dental and skeletal alterations. that can be presented. Objective: To evaluate the stages of maturation of the cervical vertebrae through the analysis proposed by Baccetti and its relationship with chronological age and sex, in lateral radiographs of individuals aged 8 to 14 years. Methodology: Cross-sectional, retrospective and descriptive study. Two hundred and eighty lateral radiographs (140 men and 140 women) were evaluated. A calibrated rater evaluated the stages of skeletal maturation and identified 6 of them. The growth peak of the individuals from the second to the fourth cervical vertebrae was evaluated on the radiographs and then related to the age and sex of the individuals. Chi square tests of association p < 0.05 were used. Results: At ages 11 and 12, it was observed that women had a higher degree of maturity than men; however, to better appreciate the results, they were regrouped according to stages: 1 with 2, 3 with 4 and 5 with 6, and statistically significant differences were found between them (p < 0.001). Conclusions: There is an association in the diagnosis of peak growth and bone maturation of patients according to their chronological age, with a clear difference between men and women, which shows that the Baccetti method can be used reliably in the population studied.